2022
DOI: 10.1039/d2bm00845a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a matchstick-shaped Au@ZnO@SiO2–ICG Janus nanomotor for light-triggered synergistic antibacterial therapy

Abstract: The drug-resistance of bacteria has posed a serious threat to public health, so the exploration of new antibacterial materials has attracted extensive attention. Here, we reported Au@ZnO@SiO2-ICG nanomotors as an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…For example, Liu et al utilized gold (Au) and zinc oxide (ZnO) to form Au@ZnO@SiO 2 -ICG matchstick-like micromotors. 98 The heterojunction formed by Au@ZnO effectively suppressed the recombination of electron-hole pairs, enhancing the generation of ROS. Under ultraviolet light irradiation, hydroxyl radicals ( OH) were generated, while under 808 nm infrared light irradiation, indocyanine green (ICG) produced singlet oxygen ( 1 O 2 ) to eliminate bacteria.…”
Section: Antibacterial Application Of Mnmsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Liu et al utilized gold (Au) and zinc oxide (ZnO) to form Au@ZnO@SiO 2 -ICG matchstick-like micromotors. 98 The heterojunction formed by Au@ZnO effectively suppressed the recombination of electron-hole pairs, enhancing the generation of ROS. Under ultraviolet light irradiation, hydroxyl radicals ( OH) were generated, while under 808 nm infrared light irradiation, indocyanine green (ICG) produced singlet oxygen ( 1 O 2 ) to eliminate bacteria.…”
Section: Antibacterial Application Of Mnmsmentioning
confidence: 99%
“…78 Furthermore, the motion of antibacterial MNMs integrated with a photocatalytic material ( e.g. BiVO 4 , 57,60 ZnO, 58,98 and Ag 3 PO 4 96 ) facilitates the generation of ROS and improves the diffusion of the antibacterial agent, thus greatly enhancing the bactericidal efficiency. On the other hand, light-based thermal fluidic manipulation can be achieved when antibacterial MNMs are composed of photothermal materials.…”
Section: Propulsion Mechanism Of Antibacterial Mnmsmentioning
confidence: 99%
“…In another report, Au@ZnO@SiO 2 -ICG (indocyanine green, a photosensitizer) nanomotor exposed to both UV and NIR light, synergizing PDT produced by UV irradiation of ZnO and PTT produced by NIR irradiation of Au & ICG, successfully penetrated the bacterial membrane and achieved an almost 100 % bactericidal rate. [13] For now, most of the photosensitizers approved for clinical cancer treatment are based on tetrapyrrole core structures, which lead to their similar disadvantages such as low water solubility, susceptibility to in vivo enzyme and photoinduced degradation, and poor cell selectivity. Recently inorganic semiconductors (TiO 2 , [14] ZnO, [15] CdSe, [16] and Cu 2 O [17] )with better stability provide new ideas for photosensitizer design.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, compared with the non‐fuel group, the MHSTU group exhibited a 20 % increase in 1 O 2 yield and a 32.9 % increase in bactericidal rate, attributed to the self‐propelled motor's ability to capture a wider range of O 2 and expand ROS distribution. In another report, Au@ZnO@SiO 2 ‐ICG (indocyanine green, a photosensitizer) nanomotor exposed to both UV and NIR light, synergizing PDT produced by UV irradiation of ZnO and PTT produced by NIR irradiation of Au & ICG, successfully penetrated the bacterial membrane and achieved an almost 100 % bactericidal rate [13] . For now, most of the photosensitizers approved for clinical cancer treatment are based on tetrapyrrole core structures, which lead to their similar disadvantages such as low water solubility, susceptibility to in vivo enzyme and photoinduced degradation, and poor cell selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Indocyanine green (ICG) is a photosensitizer with intense near-infrared (NIR) absorption, excellent singlet oxygen ( 1 O 2 ) production capacity, and low toxicity, and has been approved for clinical use by the US Food and Drug Administration (FDA). However, it exhibits poor stability when used alone and is prone to aggregation and inactivation . Meanwhile, when using a separate photothermal treatment to completely kill bacteria, the temperature needs to reach 70 °C, which will cause damage to the surrounding normal tissue and may also trigger a series of inflammatory reactions. It has been reported that the membrane permeability of bacteria is significantly enhanced by the photothermal conversion capacity induced by NIR irradiation.…”
Section: Introductionmentioning
confidence: 99%